Constitutionality In Production Sharing Contracts: Legal Policy On Petroleum And Natural Gas - Darus, Muhammad Luthfan Hadi (Prophetic Law Review, 2020)
This research is focused on constitutionality issue of Law No. 22 Year 2001 on Petroleum and Natural Gas and its relation to Article 33 of the 1945 Constitution and constitutionality of production sharing contract in relation to Article 33 of the 1945 Constitution. This research uses normative juridical method. This research founds: first, the current Law on Petroleum and Natural Gas and its relation to Article 33 of the 1945 Constitution is conceptually still problematic. This is evidenced by the several law articles which had been quashed by the Constitutional Court because they contradict the 1945 Constitution. Second, the petroleum and gas business contracts still contradict the spirit of Article 33 paragraph (3) of the 1945 Constitution, this can be seen by the granting of requests for judicial review of the Law on Petroleum and Gas in the Constitutional Court.Keywords: constitution; Production Sharing Contract (PSC); petroleum and natural gasKonstitusionalitas Dalam Kontrak Bagi Hasil: Politik Hukum Minyak Dan Gas BumiAbstrakPenelitian ini difokuskan pada masalah konstitusionalitas UU No. 22 Tahun 2001 tentang Minyak dan Gas Bumi dan kaitannya dengan Pasal 33 UUD NRI 1945 serta konstitusionalitas kontrak bagi hasil dalam kaitannya dengan Pasal 33 UUD NRI 1945. Penelitian ini menggunakan metode yuridis normatif. Penelitian ini menemukan: pertama, UU Minyak dan Gas Bumi saat ini dan kaitannya dengan Pasal 33 UUD NRI 1945 secara konseptual masih bermasalah. Hal ini dibuktikan dengan beberapa pasal undang-undang yang telah dibatalkan oleh Mahkamah Konstitusi karena bertentangan dengan UUD NRI 1945. Kedua, kontrak bisnis minyak dan gas bumi masih bertentangan dengan semangat Pasal 33 ayat (3) UUD NRI 1945. Hal ini terlihat dengan dikabulkannya permohonan uji materiil UU Minyak dan Gas Bumi di Mahkamah Konstitusi.Kata kunci: Konstitusi, Kontrak Bagi Hasil, Minyak dan Gas Bumi